Measurement of the spectral function for the $τ^-→ K^-K_Sν_τ$ decay in BABAR experiment - Sergey I. Serednyakov on behalf of the BABAR collaboration (SciPost Physics Proceedings, 2019)
The decay $τ^{-}→ K^{-}K_Sν_{τ}$ has been studied using $430×10^6$ $e^+e^-→ τ^+τ^-$ events produced at a center-of-mass energy around 10.6 GeV at the PEP-II collider and studied with the BABAR detector. The mass spectrum of the $K^{-}K_S$ system has been measured and the spectral function has been obtained. The measured branching fraction ${\cal B}(τ^{-}→ K^{-}K_Sν_{τ}) = (0.739± 0.011(\rm stat.)± 0.020(\rm syst.))× 10^{-3}$ is found to be in agreement with earlier measurements.